A novel stibium phosphate, LiBa(SbO)2(PO4)3: synthesis, crystal structure and RE3+‐activated (RE = Tb3+ and Eu3+) fluorescence performance. Issue 9 (8th August 2019) - Zhang, Shi-Rui; Zhao, Dan; Zhang, Rui-Juan; Shi, Lin-Ying; Dai, Shao-Jie; Fan, Yun-Chang
Abstract : A novel stibium phosphate, LiBa(SbO)2 (PO4 )3, featuring an [(SbO)2 (PO4 )3 ]∞ three‐dimensional open framework, can be used as a luminescent host lattice and emits green light after doping with Tb 3+ ions. Abstract : A new stibium phosphate, lithium barium bis(antimony oxide) tris(phosphate), LiBa(SbO)2 (PO4 )3, was prepared by the molten salt method with LiF as the flux. The crystal structure consists of an original three‐dimensional anionic framework of [(SbO)2 (PO4 )3 ]∞ built from PO4 tetrahedra sharing their corners with SbO6 octahedra. This framework delimits one‐dimensional tunnels where the lithium(I) and barium(II) ions are located. The UV–Vis spectrum shows that LiBa(SbO)2 (PO4 )3 was transparent from 350 to 800 nm, and is thus suitable as a luminescent host matrix. We then used Tb 3+ and Eu 3+ activators to test its luminous performance and the purities of the prepared phosphors were studied by powder X‐ray diffraction analysis with Rietveld refinements. Photoluminescence (PL) studies reveal that the emission spectra of 1 mol% RE 3+ ‐doped (RE = Tb and Eu) samples can be excited by 371 and 394 nm light, emitting green and orange–red light, respectively, for Tb 3+ and Eu 3+ . The CIE coordinates were measured to be (0.295, 0.571) and (0.6027, 0.3967), and the luminescent lifetimes were calculated as 0.178 and 1.159 ms, respectively.